The Role of the Parliamentary Government System of Bangladesh: A Special Reference from the 8th Parliament - Hossan, Md. Alomgir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The study examines how Bangladesh’s parliamentary government system functioned during the 8th Parliament and how its legislative, budgetary, and constitutional activities impacted democratic development at both national and grassroots levels, with a special focus on a ward in Rajshahi. It combines qualitative and quantitative methods, including surveys, interviews, and analysis of parliamentary documents, to assess the roles of ruling and opposition parties, patterns of political confrontation, and citizens’ perceptions of governance and accountability. The findings show that, despite intense polarization, frequent boycotts, and procedural controversies, the 8th Parliament contributed to institutional change through extensive legislation, constitutional amendment, and repeated budget cycles, while simultaneously weakening deliberative culture and inclusive participation. Survey evidence from Ward 28 of Motihar Thana reveals significant popular awareness of parliamentary activities and generally positive, though critically nuanced, attitudes toward the parliament’s contribution to democratic development. Finally, the research argues that the 8th Parliament played a contradictory but formative role, advancing formal democratic structures yet constraining substantive democratic practice in Bangladesh.